(untitled) (Bulletin KNOB, 1994)
In 1587 the curtain fell for one of the very oldest churches of Utrecht. For in that year the town council decided to pull down Salvator or Oudmunster church. The demolition started soon after the decision had been taken. This church, founded by Willibrord in the former castellum Traiectum around 700, was situated at just a very short distance to the south of St Maarten’s Dom Cathedral. In spite of the total demolition of the building, even most foundations were excavated, the church did not sink into oblivion. The church has been passed down to us through a small series of qualitatively quite reasonable illustrations of both the ground plan and the vertical elevation. The best-known illustration is the pen drawing by A. van Buchel in his ‘Monumenta passim in templis ac monasteriis Trajectinae’. Furthermore, there is an extensive description of the interior of the church by Joh. Mersman, canon of the church, and many data on the building have come down to us through the building accounts which have been handed down from 1346 onwards. A number of ordinarii, books in which the liturgical proceedings in the church are recorded, have also been preserved. In the thirties of this century the site where the eastern parts of Salvator church were once situated, was subjected to archaeological research. The results of these excavations, too, are very important to the doctoral research into this vanished church, started by me in 1991 within the framework of the so-called Dom-square project. Two other authors also take part in this research project under the leadership of A.J.J. Mekking (Leiden), who have also produced contributions to this issue of KNOB Bulletin, notably R. Rijntjes and E. van Welie. In this article I further pursue the use of dimensions in the church, as passed down to us through the dimensions indicated on the ground-plan drawings and through the archaeological research of the thirties of this century. Determining the dimensions is of great importance to further reconstruction (on paper) of the church, which is the aim of this research. Meanwhile it has become evident that the dimensions indicated in the drawings are consistent with the dimensions of the eastern parts of the church determined during the excavations. This was a reason to consider the known dimensions indicated for the western parts of the church, which have not been excavated (reasonably), reliable. The western parts of the church turned out to have quite unusual (but definitely not impossible) proportions. These curious proportions seem to have been caused by the fact that in building the western parts an older building phase was the starting point (which is quite normal), possibly even the oldest building phase, the foundation by Willibrord. It concerns a hall church of monumental dimensions, which was probably connected with a contracted annex on the east side. In the thirties remnants of walling of the supposed annex were discovered at the level of the former crossing of Salvator church and are to be dated to the eighth century without much difficulty, chiefly on the basis of the dating of a large eighth-century sarcophagus which was found within the walls. The hall church in Utrecht may have had a length of 18 metres and a width of 12 metres. Hall churches of such considerable size are rare in the eighth century, it is true, but not utterly unique. It is known that other important churches, such as the cathedral of Eichstätt (building phase I) and the church of Elst (building phase I) were large hall churches in the eighth century. The ’discovery’ of a large hall church in Utrecht detracts from the hypothesis that the missionaries could only have the disposal of small primitive churches in their missionary regions.